2006
DOI: 10.1080/14649360600715193
|View full text |Cite
|
Sign up to set email alerts
|

Fear, romance and transience in the lives of homeless women

Abstract: This paper takes up the question of what it means to be a woman who lives on the streets and in hostels as a homeless person in London. Using qualitative data from three women respondents, the analysis focuses upon their reasons for becoming and staying homeless. We address issues concerning the women's perceptions of danger and safety on the streets, the way they construct their role as women in this situation and their options for alternative ways of living in the future. We point up the strategies used by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 25 publications
1
40
0
4
Order By: Relevance
“…However, this can be a precarious and fragile practice for homeless people whose efforts for inclusion can be dismissed or rejected by housed people. For example, Radley, Hodgetts and Cullen (2006) describe a homeless woman approaching a local businessman with whom she had cultivated an acquaintance, and who had expressed an interest in her paintings. She offered to sell him a painting, but in front of a work colleague the man dismissed her approach as an 'annoying old bag lady'.…”
mentioning
confidence: 98%
“…However, this can be a precarious and fragile practice for homeless people whose efforts for inclusion can be dismissed or rejected by housed people. For example, Radley, Hodgetts and Cullen (2006) describe a homeless woman approaching a local businessman with whom she had cultivated an acquaintance, and who had expressed an interest in her paintings. She offered to sell him a painting, but in front of a work colleague the man dismissed her approach as an 'annoying old bag lady'.…”
mentioning
confidence: 98%
“…As research on single homelessness has similarly shown (May, 2000; see also Fitzpatrick, Kemp and Klinker, 2000), single homeless women are also likely to have trajectories through homelessness which reflect their mobility and ability to 'hide' their homelessness through a range of survival strategies and accommodation options outside of service networks (Klodawsky, 2006;Radley, Hodgetts and Cullen, 2006;Whitzman, 2006), although as May, Cloke and Johnsen (forthcoming; see also Radley, Hodgetts and Cullen, 2006) acknowledge, single women do remain visibly homeless on the street.…”
Section: Executive Summarymentioning
confidence: 99%
“…Homeless people tend to be unwelcome in places such as libraries and galleries, parks and shopping centres, their presence a threat to the function of that space and the ('ordinary') people inhabiting it (Radley et al, 2007). Homeless people are out of place in this public realm, and homeless women even more so: a homeless woman carrying out daily activities (washing or sleeping, for example) in a non-domestic space is conceived as particularly disturbing and transgressive.…”
Section: Challenging the Rules Of Legitimacy Regarding Occupancy Of Pmentioning
confidence: 99%